Method for producing rock wool fibers by using silicomanganese slag

Through the analysis of the chemical composition of silicon-manganese slag and the adjustment of acidity coefficient, and the determination of viscosity with the rotary cylinder method, the low production efficiency problem caused by the unconditioning of silicon-manganese slag raw materials was solved, and the efficient production of rock wool fibers was achieved, and energy consumption was reduced. and construction complexity.

CN119191716APending Publication Date: 2024-12-27NINGXIA JIYUAN JUNTAI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411405079.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The lack of chemical composition analysis and adjustment of acidity coefficient of silicon-manganese slag raw materials for producing rock wool fibers in the prior art leads to low fiber output efficiency in the subsequent production process.

Method used

By collecting and grinding silicon-manganese slag, chemical composition analysis was performed using an X-ray fluorescence spectrometer, the acidity coefficient was calculated, and the addition of silicon calcium seasoning material was used to form hot melt slag with different corrected acidity coefficients. The viscosity was measured by rotary cylinder method, and finally centrifugation was performed by centrifugation. The machine and cotton collecting mechanism are used to form plate-shaped mineral wool.

Benefits of technology

It effectively improves the correction acidity coefficient of silicon manganese slag, reduces energy consumption costs, simplifies construction technology, reduces construction difficulty and cost, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191716A_ABST
    Figure CN119191716A_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing rock wool fiber by using silicomanganese slag, which comprises the following steps: S1, collecting the silicomanganese slag obtained by smelting 100g of raw ore, grinding to obtain 200-mesh silicomanganese slag powder, and then analyzing the chemical components of the silicomanganese slag powder by using an X-ray fluorescence spectrophotometer to obtain the components SiO2, CaO, Al2O3, MnO, MgO, K2O and FeO of the silicomanganese slag powder; wherein the mass fraction of SiO2 is 39.94%, the mass fraction of CaO is 23.70%, the mass fraction of Al2O3 is 14.08%, the mass fraction of MgO is 7.81%, the mass fraction of K2O is 5.44%, and the mass fraction of FeO is 3.24%. The method effectively solves the problem that in the prior art, chemical component analysis and acidity coefficient adjustment of silicon manganese slag raw materials for producing rock wool fibers are lacked, and consequently the fiber outlet efficiency in the subsequent production process is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of producing rock wool fibers by utilizing silicomanganese slag, and relates to a method for producing rock wool fibers by utilizing silicomanganese slag. Background Art

[0002] Mineral wool products are widely used in construction, petroleum, chemical industry, electric power, metallurgy, transportation, agriculture and other industries. The chemical composition of rock wool is generally: CaO, SiO2, MgO, Al2O3, FeO, Fe2O3, TiO2, K2O, Na2O and a small amount of impurities such as S, Cl, etc. The main components are MgO, CaO, Al2O3, SiO2. The production of mineral wool should follow this principle. Mineral wool products have excellent thermal insulation, fire resistance, sound absorption and sound insulation properties, especially for energy saving. On industrial thermal equipment, every 1 cubic meter of Mineral wool products can save an average of 2,500 kcal / hour of energy, which is equivalent to saving 3 tons of standard coal per year. Using 1 ton of mineral wool products for insulation in buildings can save energy equivalent to 1 ton of oil per year. Traditional mineral wool is a fluffy short-fiber cotton made of natural rocks such as basalt, gabbro, dolomite, iron ore, bauxite, etc. as the main raw materials, which is made by high-intensity and high-temperature spraying. Natural rocks, ores and other raw materials are melted in a cupola or other pool kiln, and then blown and quenched into fibers at a pressure of 50 atmospheres. This production link consumes a lot of energy, resulting in high cost of mineral wool and poor market competitiveness.

[0003] The Chinese patent with the authorization publication number CN110128021B discloses a production method of basalt-type rock wool fiber using high-silicon silicon-manganese hot molten slag, and a production method of "basalt"-type rock wool fiber using high-silicon silicon-manganese hot molten slag. By improving the process on the basis of high-silicon silicon-manganese hot molten slag, the waste slag can be prepared into basalt-type rock wool without or with less use of regulators such as basalt and dolomite, thereby increasing the added value of the product. At the same time, the use of hot molten slag to make rock wool fibers can effectively utilize the sensible heat of hot molten slag, avoid secondary heating of waste slag or ore, and reduce the energy consumption of mineral wool; however, the technical solution lacks the chemical composition analysis of the silicon-manganese slag raw materials for producing rock wool fibers and the adjustment of the acidity coefficient, resulting in low fiber production efficiency in the subsequent production process, so there is an urgent need for a method for producing rock wool fibers using silicon-manganese slag. Summary of the invention

[0004] In view of the above problems, the present invention proposes a method for producing rock wool fiber using silicomanganese slag, which effectively solves the problem in the prior art that there is a lack of chemical composition analysis and acidity coefficient adjustment of the silicomanganese slag raw materials for producing rock wool fibers, resulting in low fiber production efficiency in the subsequent production process.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for producing rock wool fiber using silicon manganese slag, comprising the steps of:

[0007] S1. Collect 100 g of silicon-manganese slag after smelting the raw ore and grind it to obtain 200-mesh silicon-manganese slag powder, and then use X-ray fluorescence spectrometer to analyze the chemical composition of the silicon-manganese slag powder to obtain the components of the silicon-manganese slag powder SiO2, CaO, Al2O3, MnO, MgO, K2O and FeO; wherein the mass fractions of SiO2, CaO, Al2O3, MnO, MgO, K2O, FeO and impurities are 39.94%, 23.70%, 14.08%, 7.81%, 5.44%, 3.24% and 5.79% respectively;

[0008] S2, calculating the acidity coefficient of the silicomanganese slag in step S1;

[0009]

[0010] Where Mk represents the acidity coefficient, which is the mass ratio of acidic oxides to basic oxides in the raw materials; W SiO2 Indicates the mass of SiO2, W Al2O3 Indicates the mass of Al2O3, W CaO Indicates the mass of CaO, W MgO Indicates the mass of MgO;

[0011] S3, calculating the corrected acidity coefficient of the silicomanganese slag in step S1;

[0012]

[0013] Among them, Mk * Indicates the corrected acidity coefficient; W SiO2 Indicates the mass of SiO2, W Al2O3 Indicates the mass of Al2O3, W CaO Indicates the mass of CaO, W MgO Indicates the mass of MgO, W MnO Indicates the mass of MnO, W FeO Indicates the mass of FeO, W K2O represents the mass of K2O;

[0014] S4, adding a tempering material containing silicon and calcium into the heated silicon-manganese slag to form a silicon-manganese slag mixture, tempering the modified acidity coefficient of the silicon-manganese slag to different values, heating the silicon-manganese slag mixture, and finally obtaining hot molten slag with different modified acidity coefficients;

[0015] S5. Determine the viscosity of hot slag with different corrected acidity coefficients by rotating cylinder method;

[0016] S6. According to the content of step S5, the silicon-manganese slag produced after the smelting of the raw ore is added to the tempering electric furnace and a tempering material containing silicon and calcium is added. The silicon-manganese slag is tempered to obtain hot molten slag. The hot molten slag enters the centrifuge through a conveyor belt to be spun into fibers. The fibers are made into plate-shaped mineral wool by a cotton collector connected to the output end of the centrifuge. The plate-shaped mineral wool is transported to the pendulum device through a conveyor belt for compaction to form a mineral wool board. The mineral wool board is formed and cured by a forming machine and a curing furnace, and is made into a finished product by cross-cutting, longitudinal cutting and packaging equipment.

[0017] Preferably, the method of measuring the viscosity of hot slag with different corrected acidity coefficients by a rotating cylinder method comprises the following steps:

[0018] S41, mixing and briquetting the silicon-manganese slag mixture in step S4 and placing it in a graphite crucible;

[0019] S42, adjusting the position of the thermocouple in the heating furnace, positioning the top of the thermocouple in the constant temperature zone inside the heating furnace, and placing the thermocouple at the bottom of the graphite crucible;

[0020] S43, when the heating furnace in S42 is heated to 1300° C., the graphite crucible in step S41 is placed in the heating furnace, the silicon-manganese slag mixture is heated and melted, the heating furnace is heated continuously, the temperature of the heating furnace is raised to 1500° C. and then kept constant for 10 minutes, and the rotor is placed under the liquid surface of the melted silicon-manganese slag in the graphite crucible to start measuring the viscosity;

[0021] S44, lowering the temperature of the heating furnace at a rate of 4°C / min, and the computer automatically records the viscosity-temperature data of the melted silicon-manganese slag;

[0022] S45. Draw a viscosity-temperature curve of the silicomanganese slag according to the viscosity-temperature data of the silicomanganese slag in step S44.

[0023] Preferably, the acidity coefficient is controlled at 1.4-1.7.

[0024] Preferably, the original acidity coefficient of the silicomanganese slag is 1.85, and the corrected acidity coefficient is 1.33.

[0025] Preferably, the modified acidity coefficient of the silicomanganese slag is 1.5-1.6 after being tempered, and the fiber-forming viscosity of the hot molten slag discharged from the tempered electric furnace is 11-7 Pa·S.

[0026] Preferably, the corrected acidity coefficient of the silicomanganese slag is 1.6.

[0027] Preferably, the thermocouple in step S42 is a double platinum-rhodium thermocouple.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention comprehensively utilizes the waste slag produced by smelting manganese alloy, so that the waste slag is processed in a molten state, thereby reducing the step of reheating the slag and effectively reducing the energy consumption cost.

[0030] 2. The rotating cylinder method is relatively simple to determine the viscosity of hot slag with different corrected acidity coefficients. It does not require complicated equipment and tools, which reduces the construction difficulty, reduces the requirements for the skills of construction personnel, and also reduces the construction cost.

[0031] 3. Adding the tempering material containing silicon calcium into the heated silicon manganese slag to form a silicon manganese slag mixture is convenient for tempering the corrected acidity coefficient of the silicon manganese slag to different values, and heating the silicon manganese slag mixture is convenient for obtaining hot molten slag with different corrected acidity coefficients. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a schematic diagram of the process of measuring the viscosity of hot slag with different corrected acidity coefficients using the rotating cylinder method.

[0033] Figure 2 It is a schematic diagram of the X-ray fluorescence spectrometer analysis spectrum of silicon manganese slag powder of the present invention.

[0034] Figure 3 The viscosity-temperature line graph of the silicon-manganese slag of the present invention is obtained by adding a silicon-calcium-containing tempering material to the slag for tempering. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] See also Figure 1-3 The present invention provides a technical solution: a method for producing rock wool fiber using silicon manganese slag, comprising the steps of:

[0037] S1. Collect 100 grams of silicon-manganese slag after smelting the raw ore and grind it to obtain 200-mesh silicon-manganese slag powder, and then use X-ray fluorescence spectrometer to analyze the chemical composition of the silicon-manganese slag powder to obtain the components of the silicon-manganese slag powder SiO2, CaO, Al2O3, MnO, MgO, K2O and FeO; wherein the mass fractions of SiO2, CaO, Al2O3, MnO, MgO, K2O, FeO and impurities are 39.94%, 23.70%, 14.08%, 7.81%, 5.44%, 3.24% and 5.79% respectively;

[0038] S2, calculating the acidity coefficient of the silicomanganese slag in step S1;

[0039]

[0040] Where Mk represents the acidity coefficient, which is the mass ratio of acidic oxides to basic oxides in the raw materials; W SiO2 Indicates the mass of SiO2, W Al2O3 Indicates the mass of Al2O3, W CaO Indicates the mass of CaO, W MgO Indicates the mass of MgO;

[0041] S3, calculating the corrected acidity coefficient of the silicomanganese slag in step S1;

[0042]

[0043] Among them, Mk * Indicates the modified acidity coefficient; W SiO2 Indicates the mass of SiO2, W Al2O3 Indicates the mass of Al2O3, W CaO Indicates the mass of CaO, W MgO Indicates the mass of MgO, W MnO Indicates the mass of MnO, W FeO Indicates the mass of FeO, W K2O represents the mass of K2O;

[0044] S4, adding a tempering material containing silicon and calcium into the heated silicon-manganese slag to form a silicon-manganese slag mixture, tempering the modified acidity coefficient of the silicon-manganese slag to different values, heating the silicon-manganese slag mixture, and finally obtaining hot molten slag with different modified acidity coefficients;

[0045] S5. Determine the viscosity of hot slag with different corrected acidity coefficients by rotating cylinder method;

[0046] S6. According to the content of step S5, the silicon-manganese slag produced after the smelting of the raw ore is added to the tempering electric furnace and a tempering material containing silicon and calcium is added. The silicon-manganese slag is tempered to obtain hot molten slag. The hot molten slag enters the centrifuge through a conveyor belt to be spun into fibers. The fibers are made into plate-shaped mineral wool by a cotton collector connected to the output end of the centrifuge. The plate-shaped mineral wool is transported to the pendulum device through a conveyor belt for compaction to form a mineral wool board. The mineral wool board is formed and cured by a forming machine and a curing furnace, and is made into a finished product by cross-cutting, longitudinal cutting and packaging equipment.

[0047] The method of measuring the viscosity of hot slag with different corrected acidity coefficients by the rotating cylinder method comprises the following steps:

[0048] S41, firstly, the silicon-manganese slag mixture in step S4 is mixed and pressed into blocks, and then placed in a graphite crucible;

[0049] S42, adjusting the position of the thermocouple in the heating furnace, positioning the top of the thermocouple in the constant temperature zone inside the heating furnace, and placing the thermocouple at the bottom of the graphite crucible;

[0050] S43, when the heating furnace in S42 is heated to 1300° C., the graphite crucible in step S41 is placed in the heating furnace, the silicon-manganese slag mixture is heated and melted, the heating furnace is heated continuously, the temperature of the heating furnace is raised to 1500° C. and then kept constant for 10 minutes, and the rotor is placed under the liquid surface of the melted silicon-manganese slag in the graphite crucible to start measuring the viscosity;

[0051] S44, lowering the temperature of the heating furnace at a rate of 4°C / min, and the computer automatically records the viscosity-temperature data of the melted silicon-manganese slag;

[0052] S45. Draw a viscosity-temperature curve according to the viscosity-temperature data of the silicomanganese slag in step S44.

[0053] The acidity coefficient is a parameter to measure the chemical durability of mineral wool, and the acidity coefficient is controlled at 1.4-1.7.

[0054] The original acidity coefficient of silicomanganese slag is 1.85, and its corrected acidity coefficient is 1.33.

[0055] The corrected acidity coefficient of silicon manganese slag is 1.5-1.6 after tempering, and the fiber-forming viscosity of the hot molten slag discharged from the tempered electric furnace is 11-7Pa·S.

[0056] The corrected acidity coefficient of silicomanganese slag is 1.6, and the long slag property, that is, the viscosity of silicomanganese slag increases slowly with decreasing temperature, and there is no obvious turning point.

[0057] The thermocouple in step S42 is a double platinum-rhodium thermocouple.

[0058] like Figure 2 In the X-ray fluorescence spectrometer analysis of the silicomanganese slag, it can be concluded that the silicomanganese slag mainly exists in an amorphous glass phase, and a small amount of magnesia-calcium siliceous stone mineral phase is precipitated, which is convenient for analyzing the chemical composition of the silicomanganese slag and thus facilitating the tempering of the silicomanganese slag.

[0059] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for producing rock wool fiber using silicon manganese slag, characterized in that: Includes steps: S1. Collect 100 g of silicon-manganese slag after smelting the raw ore and grind it to obtain 200-mesh silicon-manganese slag powder, and then use X-ray fluorescence spectrometer to analyze the chemical composition of the silicon-manganese slag powder to obtain the components of the silicon-manganese slag powder SiO2, CaO, Al2O3, MnO, MgO, K2O and FeO; wherein the mass fractions of SiO2, CaO, Al2O3, MnO, MgO, K2O, FeO and impurities are 39.94%, 23.70%, 14.08%, 7.81%, 5.44%, 3.24% and 5.79% respectively; S2, calculating the acidity coefficient of the silicomanganese slag in step S1; Where Mk represents the acidity coefficient, which is the mass ratio of acidic oxides to basic oxides in the raw materials; W SiO2 Indicates the mass of SiO2, W Al2O3 Indicates the mass of Al2O3, W CaO Indicates the mass of CaO, W MgO Indicates the mass of MgO; S3, calculating the corrected acidity coefficient of the silicomanganese slag in step S1; Among them, Mk * Indicates the corrected acidity coefficient; W SiO2 Indicates the mass of SiO2, W Al2O3 Indicates the mass of Al2O3, W CaO Indicates the mass of CaO, W MgO Indicates the mass of MgO, W MnO Indicates the mass of MnO, W FeO Indicates the mass of FeO, W K2O represents the mass of K2O; S4, adding a tempering material containing silicon and calcium into the heated silicon-manganese slag to form a silicon-manganese slag mixture, tempering the modified acidity coefficient of the silicon-manganese slag to different values, heating the silicon-manganese slag mixture, and finally obtaining hot molten slag with different modified acidity coefficients; S5. Determine the viscosity of hot slag with different corrected acidity coefficients by rotating cylinder method; S6. According to the content of step S5, the silicon-manganese slag produced after the smelting of the raw ore is added to the tempering electric furnace and a tempering material containing silicon and calcium is added. The silicon-manganese slag is tempered to obtain hot molten slag. The hot molten slag enters the centrifuge through a conveyor belt to be spun into fibers. The fibers are made into plate-shaped mineral wool by a cotton collector connected to the output end of the centrifuge. The plate-shaped mineral wool is transported to the pendulum device through a conveyor belt for compaction to form a mineral wool board. The mineral wool board is formed and cured by a forming machine and a curing furnace, and is made into a finished product by cross-cutting, longitudinal cutting and packaging equipment.

2. The method for producing rock wool fiber using silicomanganese slag according to claim 1, characterized in that: The method of measuring the viscosity of hot slag with different corrected acidity coefficients by the rotating cylinder method comprises the following steps: S41, firstly, the silicon-manganese slag mixture in step S4 is mixed and pressed into blocks, and then placed in a graphite crucible; S42, adjusting the position of the thermocouple in the heating furnace, positioning the top of the thermocouple in the constant temperature zone inside the heating furnace, and placing the thermocouple at the bottom of the graphite crucible; S43, when the heating furnace in S42 is heated to 1300° C., the graphite crucible in step S41 is placed in the heating furnace, the silicon-manganese slag mixture is heated and melted, the heating furnace is heated continuously, the temperature of the heating furnace is raised to 1500° C. and then kept constant for 10 minutes, and the rotor is placed under the liquid surface of the melted silicon-manganese slag in the graphite crucible to start measuring the viscosity; S44, lowering the temperature of the heating furnace at a rate of 4°C / min, and the computer automatically records the viscosity-temperature data of the melted silicon-manganese slag; S45. Draw a viscosity-temperature curve according to the viscosity-temperature data of the silicomanganese slag in step S44.

3. The method for producing rock wool fiber using silicomanganese slag according to claim 1, characterized in that: The acidity coefficient is controlled at 1.4-1.

7.

4. The method for producing rock wool fiber using silicomanganese slag according to claim 1, characterized in that: The original acidity coefficient of silicomanganese slag is 1.85, and its corrected acidity coefficient is 1.

33.

5. The method for producing rock wool fiber using silicomanganese slag according to claim 1, characterized in that: The corrected acidity coefficient of silicon manganese slag is 1.5-1.6 after tempering, and the fiber-forming viscosity of the hot molten slag discharged from the tempered electric furnace is 11-7Pa·S.

6. The method for producing rock wool fiber using silicomanganese slag according to claim 5, characterized in that: The corrected acidity coefficient of silicomanganese slag is 1.

6.

7. The method for producing rock wool fiber using silicomanganese slag according to claim 2, characterized in that: The thermocouple in step S42 is a double platinum-rhodium thermocouple.